A Stall Only on the Surface? Working Hours and the Persistence of the Gender Wage Gap in Western Germany 1985–2014. (18th February 2022) - Schmitt, Laila; Auspurg, Katrin
Abstract: To what extent has the closing of the gender gap in hourly wages ('gender wage gap'; GWG) in Western Germany stalled due to an increasing supply of non-standard working hours? We use descriptive trend analyses and Juhn–Murphy–Pierce decompositions of German Socio-Economic Panel data for the last 30 years (1985–2014) to analyse the extent to which the expansion of part-time and marginal work, as well as overwork, may have contributed to the dynamics of the GWG in Western Germany. We find that the large increase in part-time work among women in combination with increasing wage gaps between part-time and full-time work substantially widened the GWG (by about one-sixth). Working hour effects were large enough to offset the equalizing effects of declining gender gaps in human capital, and they existed even in the public sector. In contrast to the United States, trends in overwork did not have a meaningful impact on the GWG. In an add-on, we find a widening of the gender gap in monthly earnings, but also an important closing of the gender earnings gap unconditional on employment due to an increased labour supply of women. Our results suggest that working hours should be given more consideration in research on family–work conflict and gender earnings inequalities.